EFFECTS OF ACUTE NORMOBARIC HYPOXIA-INDUCED PULMONARY HYPERTENSION ON ELECTROCARDIGRAPHIC MEASURES IN POST-MYOCARDIAL INFARCTION PATIENTS. (June 2022) - Kramer, Tilmann; Hoenemann, Jan; Weis, Henning; Jordan, Jens; Tank, Jens; Rosenkranz, Stephan; Baldus, Stephan; Limper, Ulrich
Abstract : Objective: Normobaric hypoxia induces pulmonary hypertension (PH) in healthy individuals and post-myocardial infarction (P-MI) patients. Depending on the size of the myocardial scar and the remaining left ventricular ejection fraction, P-MI patients are potentially more vulnerable to cardiac rhythm disorders than healthy individuals. Albeit of utmost importance for P-MI patients planning high altitude sojourn, data regarding effects of hypoxia on cardiac rhythm remain contradictory. The objective was to evaluate if normobaric hypoxia-induced PH triggers electrocardiographic changes at rest and under exertion in P-MI patients. Design and method: At the German Aerospace Center:envihab facility, 4 non-professional male athletes (57.8 ± 3.3years) in clinically stable condition after left ventricular ST-elevation MI (3 type I and 1 type II MI, all> 1 year since event) and subsequent drug-eluting stent implantation for single-vessel coronary artery disease were exposed to normobaric hypoxia achieved by nitrogen dilution. Starting at 20.9%, oxygen content was gradually decreased to a minimum of 11.5% over a period of 19 days. Within the following 3 days hypoxia was stepwise reduced back to 20.9% oxygen. Standard 12-lead resting electrocardiogram (ECG) and transthoracic echocardiography (TTE) were performed daily. For echocardiographic detection of PH, systolic pulmonary arterial pressure (sPAP) was measured. Exercise ECG was performed under normoxia and under 17.5% oxygen. Results: Normobaric hypoxia with a minimum of 11.5% O2 led to elevated sPAP in TTE. Echocardiographic signs of PH were closely linked to significantly increased QTc interval using Bazett's (from 402 ± 13 to 417 ± 25ms) and Holzmann's (103 ± 4 to 107 ± 6%) formula compared to normoxia (all p < 0.01). In exercise ECG under hypoxia, an increased number of ventricular and supraventricular extrasystoles could be detected compared to normoxia. Conclusions: In clinically stable P-MI patients, exposure to normobaric hypoxia leading to PH significantly prolongs corrected QT interval and potentially triggers cardiac arrhythmias like premature beats under exertion. P-MI patients should undergo echocardiography and exercise electrocardiography in suitable facilities under hypoxic conditions prior to planned high altitude sojourn. Particularly P-MI patients with prolonged QTc interval under normoxia appear susceptible to cardiac arrhythmias due to the additional QTc interval-prolonging effect under hypoxia. Further studies are pending in this context.